Analysis of Salivary Gland Cancer before and during the COVID-19 Pandemic in Brazil - Vitória Ferreira Leite; Débora Rosana Alves Braga Silva Montagnoli; Yasmim Silva Godoy; Alex Júnio Silva Cruz; Maria Cássia Ferreira Aguiar; Mauro Henrique Nogueira Guimarães Abreu; Renata Castro Martins (Revista Brasileira de Cancerologia)
Introduction: The COVID-19 pandemic has harmed health services, including delays in diagnosing and beginning of cancer treatment. Objective: To analyze and compare the number of salivary gland cancer (SGC) case registrations, staging and time to start treatment (TT) from 2019 to 2022 in Brazil. Method: Data on SGC registrations, gender, age group, type of treatment, staging, and TT were collected from the Oncology Panel. A descriptive analysis of the variables was carried out and the Friedman test was used to compare the number of SGC, staging, and TT records of the years analyzed (p < 0.05), using SPSS v.22.0. Results: For the period investigated, SGC records were more prevalent in males from the fifth decade of life onwards; surgery and radiotherapy were the most frequent therapeutic modalities, and stages IV and III were the most prevalent whenever staging was recorded. TT < 30 days was predominant in all periods, followed by TT > 60 days. SGC, staging and TT records showed median variations between pre- and trans-pandemic periods, but without statistically significant differences (p > 0.05). Conclusion: No significant differences were identified in SGC, staging, and TT records in Brazilian states before and during the COVID-19 pandemic. These results suggest that the Brazilian public health system managed to maintain consistent cancer care, even during the COVID-19 pandemic.